WASHBACK AND THE ASSESSMENT PRACTICES OF ESL INSTRUCTORS AT JAPANESE UNIVERSITY - Lee Hughes (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study investigated awareness among native-English instructors teaching English to first year freshman students studying English at a university in Japan, and the potential effects of their chosen methods of oral evaluation on washback. Washback effect refers to the impact of testing – whether positive or negative - on teaching practices, curriculum design, and learning behaviors.  Oral washback, in particular, in evaluation has seen increased importance in recent years, with more consideration given to how to provide positive oral washback in evaluations to ensure that they are as effective as possible in improving English levels. A mixed methods approach was used – a survey and interviews – with five instructors to find out about how they assess their students and how aware and how much attention they gave to possible washback effects of their chosen methods of evaluation. It was found that there is quite a variance among different instructors and knowing more about how to promote more positive oral washback to be useful in improving evaluation methods used.